Evaluation of the presence of SARS-CoV-2 in vaginal and anal swabs of women with omicron variants of SARS-CoV-2 infection - Liu, Ding; Zhang, Yunfu; Chen, Dongfeng; Wang, Xianhua; Huang, Fuling; Long, Ling; Zheng, Xiuhui (Frontiers in Microbiology, 2022)
Objectives: The study aimed to determine whether SARS-CoV-2 Omicron variant could be detected in the vaginal fluid and anal swabs of reproductive-aged and postmenopausal women infected with SARS-CoV-2 Omicron variant. Methods:Included in this study were 63 women who were laboratory confirmed as having SARS-CoV-2 Omicron variant infection and admitted to the responsible ward of Daping Hospital of at the National Exhibition and Convention Center(Shanghai) Makeshift Hospital from May 1-24, 2022.From them, vaginal and anal swabs were obtained with informed consent. The demographic and baseline clinical characteristics and the swab test results were analyzed. Results: The 63 included patients ranged in age from 18 to 72 years with a median of 47.71±15.21 years. Of them, 38 women (60.3%) were in their reproductive years. Most of the participants (77.8%) were healthy without significant underlying diseases. Fourteen patients (22.2%) had asymptomatic infection and the remaining 49 (77.8%) had mild infection. The upper respiratory tract symptoms including cough(40/63.5%) and sore throat (18/28.6%)were the most common clinical manifestations of these mildly infected patients. Only 5 patients (7.8%) had gastrointestinal (GI) symptoms, including simple diarrhea in 4 patients, and diarrhea with vomiting in one patient. Pharyngeal,vaginal and anal swabs were collected simultaneously from all 63 patients 8-16 (mean 11.25±2.23) days after SARS-Cov-2 Omicron variant infection. The vaginal swabs were negative for SARS-CoV-2 in all 63 patients, and the anal swabs were positive in 4 patients (6.5%). The overall median hospitalization duration was 16.73±3.16 days. Conclusions:The results of the present study suggest that there is a low possibility of SARS-Cov-2 Omicron variant transmission via the digestive tract and vaginal fluid. The correlation between the GI symptoms and the presence of viral RNA in anal swabs is uncertain.